Management Of Sports Tourism Management In Mentawai Islands - Anton Komaini; Endang Sepdanius; Pudia M. Indika; Hijriyantomi Suyuthie (International Journal of Tourism, Heritage and Recreation Sport, 2019)
Mentawai Islands Regency is one of the areas in West Sumatra that develops sports tourism, among the tourism sports developed by the Mentawai Islands Regency are surfing (diving), diving (fishing), fishing (fishing), beach tourism, trekking along inland Mentawai forest. The purpose of this study was to determine the management of tourism sports in the Mentawai Islands District. This research is a type of descriptive research that aims to reveal the data encountered in the field. This research was carried out at the Mentawai Islands Regency Tourism Office. The sample in this study were 16 people. Variables that will be examined include organizing, promotion and infrastructure. The technique used to collect data is a Guttman questionnaire and interviews. The results of the study concluded that 1) The management of organizing sports tourism in the Mentawia Islands was in a fairly good category with an achievement rate of 59.38%, 2). The promotion carried out by the Department of Youth Tourism and Sports in the Mentawai Islands District was in a good category with an achievement rate of 62.5% . 3) The level of achievement of facilities and targets in the management of sports tourism in the Mentawai Islands is 40.18%, this is included in the less category.